Is Menstruation Still a Dark Side of the Society in 21th Century in Nepal? (Siddhajyoti Interdisciplinary Journal, 2020)
Menstruation is a natural and biological phenomenon, but our patriarchal Nepalese society has practiced different taboos during the menstruation. Due to the taboos, women are deprived of different physical and psychological problems in this period. People are not much discussing the menstrual issues in their home and societies. The aim of this study is to explore the existing practices, prevailing knowledge, source of information and problems facing by girl sat their home and school. In-depth interview was conducted from the purposively selected students from Gongabu Health Post Kathmandu. Collected data were analysed on thematic basis and relevant themes were generated. Study shows that students had a poor knowledge about menarche. Lack of awareness and preparedness most of them used traditional pad during the menstruation and were frightened on their menarche. There are still several taboos about menstruation in different parts of the country and ethnic groups which act for women deprivation to the progress and grip the opportunity.